The Main Property of Heat Storage Materials and their Compatibility in Them of the Heat Exchanger - Makhmudovich, Makhmudov Razmat; Ibragimovna, Kholmurodova Zebo; Azzamovich, Usmonov Shavkat; Shernazovich, Babanazarov Sanzhar (European Journal of Life Safety and Stability (2660-9630), 2021)
The article under consideration is devoted to the study of the variety of thermal energy accumulators in terms of the time of use of the daily, weekly and seasonal type, as well as the heat-accumulating materials used in them, their thermophysical properties, the nature of the behavior of crystal hydrates of salts and their field of application. In addition, the analysis of the compatibility of heat storage materials with the materials of heat exchangers included in the thermal energy accumulator to intensify the heat exchange process has been carried out.